The modified gravity light-cone simulation project: I. Statistics of matter and halo distributions - Arnold, Christian; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We introduce a set of four very high resolution cosmological simulations exploring f(R) gravity, with 20483 particles in 768 and $1536 \, h^{-1} \, {